2021
DOI: 10.3390/diagnostics11071230
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and Inter-Rater Reliability of Strength Measurements Using a Pull Hand-Held Dynamometer Fixed to the Examiner’s Body and Comparison with Push Dynamometry

Abstract: Hand held dynamometers (HHDs) are the most used method to measure strength in clinical sitting. There are two methods to realize the assessment: pull and push. The purpose of the present study was to evaluate the intra- and inter-rater reliability of a new measurement modality for pull HHD and to compare the inter-rater reliability and agreement of the measurements. Forty healthy subjects were evaluated by two assessors with different body composition and manual strength. Fifteen isometric tests were performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
5
2
Order By: Relevance
“…However, considering the missing data (no 95% CI provided) and the use of a different protocol in Kilmer's study, comparisons with our results are not possible (36). As for the reliability of the hip internal rotators, a few studies have been conducted with variable results (23,26,37). Unlike our results, Gonzalez-Rosalen et al (23) showed excellent inter-rater reliability.…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…However, considering the missing data (no 95% CI provided) and the use of a different protocol in Kilmer's study, comparisons with our results are not possible (36). As for the reliability of the hip internal rotators, a few studies have been conducted with variable results (23,26,37). Unlike our results, Gonzalez-Rosalen et al (23) showed excellent inter-rater reliability.…”
Section: Discussioncontrasting
confidence: 57%
“…As for the reliability of the hip internal rotators, a few studies have been conducted with variable results (23,26,37). Unlike our results, Gonzalez-Rosalen et al (23) showed excellent inter-rater reliability. In contrast, Thorborg et al (37) revealed similar results to ours, with fair to excellent inter-rater reliability and no agreement between testers.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…EasyForce is purported to allow practitioners to measure muscle force objectively, and thus reducing the need for subjective measures and providing valuable data to aid in the design of treatment plans. Moreover, Easyforce is a dynamometer specifically designed for belt-stabilized HHD, which is of great importance, having in mind that stabilizing dynamometers with belts has shown better reliability and validity [ 34 , 35 ]. However, the vast majority of literature on HHD has focused on devices that are not integrated within the belt.…”
Section: Introductionmentioning
confidence: 99%